2021
DOI: 10.3390/jcm10040691
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Arterial Stiffness One Month after Bariatric Surgery and Potential Mechanisms

Abstract: Arterial stiffness (AS) is an independent predictor of cardiovascular risk. We aimed to analyze changes (Δ) in AS 1-month post-bariatric surgery (BS) and search for possible pathophysiological mechanisms. Patients with severe obesity (43% hypertensives) were prospectively evaluated before and 1-month post-BS, with AS assessed by pulse-wave velocity (PWV), augmentation index (AIx@75) and pulse pressure (PP). Ambulatory 24 h blood pressure (BP), anthropometric data, renin-angiotensin-aldosterone system (RAAS) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Similar to previous research [16,44,[54][55][56], our subjects have also shown a marked improvement in PWA parameters and, as such, a reduction of the general arterial stiffness (AS). Nevertheless, other studies did not find such changes in the AS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous research [16,44,[54][55][56], our subjects have also shown a marked improvement in PWA parameters and, as such, a reduction of the general arterial stiffness (AS). Nevertheless, other studies did not find such changes in the AS.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, in their study, Jamialahmadi et al, have observed a significant decline of PWV, post-bariatric surgery [16]. It is well-known that AS may be one of the mechanisms by which obesity increases cardiovascular risk independently of traditional risk factors [55]. However, this parameters can be assessed using various methodologies.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it was found that 5 % weight loss is associated with 27 % reduction in angiotensinogen levels, 43 % reduction in renin, 31 % decrease in aldosterone, 12 % decrease in ACE activity, and 20 % decrease in angiotensinogen expression in the adipose tissue [116]. Consistently, it has been observed that decreased arterial stiffness and blood pressure after bariatric surgery is associated with a significant reduction in plasma renin activity and plasma aldosterone [118,119].…”
Section: Raas Overactivitymentioning
confidence: 76%
“…Weight loss, one month after bariatric surgery, in patients with severe obesity, significantly improved arterial stiffness. Changes in some components of RAAS were independent correlates for the final values of vascular parameters, suggesting the involvement of this system in obesity-associated arterial stiffness [ 112 ].…”
Section: Proinflammatory Cytokines and Arterial Stiffnessmentioning
confidence: 99%